Nigeria: In-depth assessment of extension and advisory services: Developing Local Extension Capacity (DLEC) project - Huber, Sarah; Davis, Kristin E.; Lion, Karin (Digital Green, 2017)
This report presents an in-depth analysis of the extension and advisory services (EAS) system in Nigeria. The document produces actionable recommendations for improvement of EAS using the “best-fit” framework that examines the services from a systems perspective and then analyzes the EAS system through six EAS characteristics – the governance structures and policy environment; organizational and management capacities and cultures; advisory methods; market engagement; livelihood strategies; and community engagement. The recommendations are intended for any EAS stakeholder interested to improve extension, be they federal or state governments, donors, the private sector, nongovernmental organizations (NGOs) or others. This report is based on a literature review on the Nigerian extension system and interviews with a variety of EAS actors during the period November 2016 - January 2017.